MNCs' corporate environmental responsibility in emerging and developing economies: Toward an action research approach. Issue 2 (6th June 2019) - Becker-Ritterspach, Florian; Simbeck, Katharina; El Ebrashi, Raghda
Abstract : Purpose: This paper aims to provide multinational corporations (MNCs) with a portfolio of corporate environmental responsibility (CER) responses that help curbing the exacerbated negative environmental externalities caused by their business activities in emerging and developing economies. Design/methodology/approach: This paper transposes the market-related concept of institutional voids to the context of CER, that is, to the context of exacerbated negative environmental externalities as result of absent, weak or incoherent institutions. Findings: This paper proposes that the transfer of products, processes and business models from developed to emerging or developing economies often gives rise to exacerbated negative externalities because of institutional voids in environmental protection. Thus, it suggests a portfolio of CER responses – circumventing, coping and compensating – that allow MNCs to mitigate the exacerbated negative environmental externalities caused by them. Research limitations/implications: The authors present an analytical framework for identifying and navigating environment related institutional voids, which serves as a starting point for an action research approach. In tune with recent calls for critical performativity in critical management studies, the action research approach aims at tackling the real-life problem of exacerbated negative environmental externalities caused by MNCs' activities in emerging and developing economies. Social implications: This paper sensitizes scholars, policymakers and managers to exacerbated negative environmental externalities within the context of international business activities in emerging and developing economies. The contribution provides stakeholders with a better understanding of the causes as well as alternative responses to the problem. Originality/value: This paper transposes the market-related concept of institutional voids and the strategic responses to dealing with them to the non-market context of CER. The authors argue that institutional voids can be seen as the absence or poor functioning of formal and informal institutions for environmental protection, resulting in exacerbated negative environmental externalities.